Contribuições ao uso de tório em reatores de água pressurizada - aspectos neutrônicos - Víctor Faria de Castro (2020)
In this work, the neutronic feasibility of using a reprocessed fuel spiked in thorium in existing PWR was evaluated. Using the SCALE 6.0 nuclear code package, the analysis was performed based on neutronic parameters such as the neutronic multiplication factor, reactivity coefficients of temperature and delayed neutron fraction, and the isotopic composition over a burnup cycle. First, a standard PWR was modelled based on the FSAR of Angra 2. The infinite multiplication factor was obtained, which is the main parameter during the analysis of the core. The reprocessed fuel obtained using the UREX+ technique was spiked in thorium with several concentrations and inserted into the standard core, replacing the UO2 fuel. After the criticality analyses using the KENO-VI code were carried out, burnup calculations were performed by ORIGEN-S, both part of the SCALE 6.0 package. Initially, the core as a whole was evaluated, followed by the fuel elements evaluation. In this latter step, NEWT code was also used for neutron transport in order to obtain physical parameters for generating homogenized cross-sections. Afterwards, supercell analyses were performed using the proposed fuel. In the final part of the work, the core was remodelled with the removal of the IFBA rods. The results show that the use of the proposed fuel reduces the negative temperature reactivity coefficient, as well as the delayed neutron fraction when compared to the standard UO2 fuel. Acknowledgement of these fundamental safety parameters indicates that the safety control systems that are applied in standard PWR need to be revaluated. It is also verified that the introduction of reprocessed fuel spiked in thorium introduces some advantages, such as the possibility of extending the burnup and removal of the burnable poison. Furthermore, the selected reprocessing technique UREX+ complies with non-proliferation treaties and reduces waste resulting from an open fuel cycle. This work, part of a larger project that aims to assess the feasibility of the use of thorium in existing PWR, introduces new approaches in this area by studying the introduction of reprocessed fuel spiked in thorium. In all calculations performed using NEWT, homogenised cross-sections were generated for subsequent use in nodal codes, such as PARCS, followed by a neutronic/thermal-hydraulic coupling analysis, i.e., PARCS/RELAP.